2021
DOI: 10.1159/000518611
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implementation and Initial Experience of Neutrophil Gelatinase-Associated Lipocalin Testing for the Diagnostic and Prognostic Assessment of Acute Kidney Injury Events in Hospitalized Patients

Abstract: <b><i>Introduction:</i></b> The use of novel kidney injury biomarkers has been shown to improve diagnostic assessment and prognostic prediction in various populations with acute kidney injury (AKI), but their use in a standard clinical practice have been rarely reported. <b><i>Methods:</i></b> We reported the clinical implementation of neutrophil gelatinase-associated lipocalin (NGAL) measurement for routine AKI diagnostic workup of patients receiving nephrology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…There is limited use of kidney injury biomarkers in a clinical context. However, some nephrologists have recently begun to use neutrophil gelatinase-associated lipocalin (NGAL) to improve diagnostic discrimination and aid management of AKI in routine clinical practice (13). Cote et al reported on the use of plasma and urinary NGAL in a heterogeneous cohort of AKI patients in their institution.…”
Section: Methodology Of Aki Diagnosismentioning
confidence: 99%
“…There is limited use of kidney injury biomarkers in a clinical context. However, some nephrologists have recently begun to use neutrophil gelatinase-associated lipocalin (NGAL) to improve diagnostic discrimination and aid management of AKI in routine clinical practice (13). Cote et al reported on the use of plasma and urinary NGAL in a heterogeneous cohort of AKI patients in their institution.…”
Section: Methodology Of Aki Diagnosismentioning
confidence: 99%
“…Urine NGAL (uNGAL) and plasma NGAL (pNGAL) could be measured, but uNGAL was generally preferred based on previous experiences showing a lower specificity and overall accuracy for pNGAL in hospitalized patients with already confirmed AKI. 8 The NGAL was validated and measured using an automated AU5800 Chemistry Analyzer (BeckmanCoulter © ) with the NGAL Test™ by BioPorto Diagnostics © (Hellerup, Denmark) by turbidimetric immunoassay. The limit of quantification and measurable ranges for both uNGAL and pNGAL were 25 to 3000 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Indeed, the presence of tubular damage biomarkers such as the neutrophil gelatinase-associated lipocalin (NGAL) is clinically associated with intrinsic AKI, mostly acute tubular injury, while its absence is more in favor of functional (prerenal) causes. 7 , 8 Recently, the 23nd Acute Disease Quality Initiative Consensus Conference recommended that a combination of functional and damage biomarkers should now be integrated with clinical information, to identify high-risk patients and to improve diagnostic assessment and management of AKI episodes in various clinical settings. 9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations